Serum IgG Antibodies against Periodontal Microbes and Cancer Mortality. (April 2020) - Zhong, Z.; Jin, Q.; Zhang, J.; Park, Y.M.; Shrestha, D.; Bai, J.; Merchant, A.T.
Introduction: Periodontitis is a chronic inflammatory condition initiated by microorganisms and is positively linked to systemic conditions such as cancer, cardiovascular disease, and diabetes mellitus. Objectives: To prospectively investigate associations between empirically derived clusters of IgG antibodies against 19 selected periodontal microorganisms and cancer mortality in a representative sample of the US population. Methods: We evaluated 6, 491 participants aged ≥40 y from the Third National Health and Nutrition Examination Survey (1988 to 1994), who had complete data on IgG antibody titers against 19 selected periodontal microorganisms and were free of cardiovascular disease and cancer. In a prior study, antibodies were categorized into 4 mutually exclusive groups via cluster analysis: red-green, orange-red, yellow-orange, and orange-blue. Cluster scores were estimated by summing z scores of the antibody titers making up each cluster. Participants were followed up to death until December 31, 2011. Cox proportional hazard models were applied to estimate hazard ratios (HRs) and 95% CIs for all-cancer mortality by tertiles of cluster scores. Results: During follow-up for a median of 15.9 y, there were 2, 702 deaths (31.3%), including 631 cancer-related deaths (8.1%). After adjusting for multiple confounders, the orange-blue cluster was inversely associated with cancer mortality (tertile 2 vs. tertile 1: HR = 0.67, 95% CI = 0.54 to 0.84; tertile 3 vs tertile 1: HR = 0.62, 95% CI = 0.46 to 0.84). The association between the yellow-orange cluster and all-cancer mortality was also inverse but not significant, and the orange-red cluster and the red-green cluster were not associated with all-cancer mortality. Conclusions: Antibodies against Eubacterium nodatum and Actinomyces naeslundii may be novel predictors of cancer mortality. If further studies establish a causal relationship between these antibodies and cancer mortality, they could be targets to prevent possible systemic effects of periodontal disease with potential interventions to raise their levels. Knowledge Transfer Statement: Periodontal antibodies against Eubacterium nodatum and Actinomyces naeslundii were inversely associated with cancer mortality among adults followed up for an average of 16 y. Periodontal antibodies may predict cancer mortality.